If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + 4 = a Reorder the terms: 4 + a = a Add '-1a' to each side of the equation. 4 + a + -1a = a + -1a Combine like terms: a + -1a = 0 4 + 0 = a + -1a 4 = a + -1a Combine like terms: a + -1a = 0 4 = 0 Solving 4 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 4b+3=7 | | 4m^2-5=95 | | 2x+1x=126 | | (7)+11= | | -5+4a^2=59 | | 3+2t-1=6t+10-2t | | 16n^2-2=14 | | x+26=3x+26 | | 0.19x-1.57=0.46x | | 2x(x+3)=(3x+1)(x+1) | | 0.3(x+100)+1.5x=111 | | 25x8/2727 | | -b-3=-8 | | 0*6×12/3-1 | | 12x^3+28x^20-23x+3=0 | | 3(9k-6)=25-7k | | 0.42-0.21x=0.45x-486 | | 0.3(x+100)+1.5x=11 | | 3,8x/14=3/14/3 | | 5x+4=6x^2 | | 12x^3-34x^2-5678x-9=0 | | y(y-7)=2(5-2y) | | -6x(4x-7y^2+3)= | | -6m^2+8m+8=0 | | log4X=3/2 | | (x-5)(x+2)=-10 | | 3/5-1=8/5w | | 20-0.375q=-76.6 | | Y^2dX/dY=1/X^3 | | 4x-8=6x-9 | | 6y^2=-7y+3 | | 0.5=(1800*(243.84^3))/((10*10^6)*48*((b*(9.525^3)-(b-1.27)*(8.255^3))/12)) |